2000
DOI: 10.1152/jappl.2000.89.4.1275
|View full text |Cite
|
Sign up to set email alerts
|

Upper airway muscle responsiveness to rising Pco2during NREM sleep

Abstract: Although pharyngeal muscles respond robustly to increasing PCO(2) during wakefulness, the effect of hypercapnia on upper airway muscle activation during sleep has not been carefully assessed. This may be important, because it has been hypothesized that CO(2)-driven muscle activation may importantly stabilize the upper airway during stages 3 and 4 sleep. To test this hypothesis, we measured ventilation, airway resistance, genioglossus (GG) and tensor palatini (TP) electromyogram (EMG), plus end-tidal PCO(2) (PE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
55
1
3

Year Published

2002
2002
2023
2023

Publication Types

Select...
6
2
1

Relationship

4
5

Authors

Journals

citations
Cited by 71 publications
(61 citation statements)
references
References 34 publications
2
55
1
3
Order By: Relevance
“…5, 9, 46) and human studies (e.g., Refs. 31,32,47). The excitation of hypoglossal motoneurons achieved with increased ventilation is consistent with the effect produced at the motoneuron pools of the parasternal intercostals and scalenes that show more prominent recruitment than frequency modulation (16).…”
Section: Discussionsupporting
confidence: 72%
“…5, 9, 46) and human studies (e.g., Refs. 31,32,47). The excitation of hypoglossal motoneurons achieved with increased ventilation is consistent with the effect produced at the motoneuron pools of the parasternal intercostals and scalenes that show more prominent recruitment than frequency modulation (16).…”
Section: Discussionsupporting
confidence: 72%
“…In general, upper airway obstruction elicits compensatory neuromuscular responses that maintain upper airway patency and prevent sleep apnea from developing. These responses can restore airway patency by recruiting muscles that dilate and elongate the airway (63,65,66,67,(78)(79)(80)(81)(82)(83)(84). In patients with sleep apnea, impaired neural responses to airway obstruction account for the marked elevation in Pcrit during sleep compared with normal individuals (54)(55)(56).…”
Section: Obesity and Upper Airway Neuromechanical Control Modeling Upmentioning
confidence: 99%
“…Since the pioneering studies of REMMERS et al [18], it is believed that the forces preventing pharyngeal obstruction are produced primarily by the upper airway dilator muscles. The reduction in GG-EMG activity with the onset of sleep [8,9] and the diminution of the reflex response of the GG to negative pressure [19] and chemical drive [20] during sleep suggested that the increase in pharyngeal collapsibility during sleep is due primarily to sleep-associated decrease in dilator muscle activity.…”
Section: Sleep-related Disorders Y Dotan Et Almentioning
confidence: 99%